2020
DOI: 10.1021/acssensors.0c00399
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Complex Emulsions as Amplifiers for On-Chip Photonic Cavity-Enhanced Resonators

Abstract: Despite the recent emergence of microcavity resonators as label-free biological and chemical sensors, practical applications still require simple and robust methods to impart chemical selectivity and reduce cost of fabrication. We introduce the use of hydrocarbon-in-fluorocarbon-inwater (HC/FC/W) double emulsions as a liquid top cladding that expands the versatility of optical resonators as chemical sensors. The all-liquid complex emulsions are tunable droplets that undergo dynamic and reversible morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…the droplet geometries can be controllably altered after emulsification by triggering changes in the surfactant effectiveness, 15,16 and examples of the latter include stimuli-responsive or cleavable surfactants. 17 Owing to this unique morphological response to targeted chemical stimuli, Janus emulsions have been exploited in a number of applications, including as tunable microlenses, 18 optical waveguides, [19][20][21] scaffolds for the fabrication of anisotropic solid objects, 22,23 motile particle systems, 24,25 and as transducers and signal amplifiers in improved chemo-and biosensing platforms. [26][27][28][29] Herein, we leverage the exquisitely sensitive chemicalmorphological coupling inside Janus emulsions for the development of a new simple and broadly applicable method for the quantitative characterization of surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…the droplet geometries can be controllably altered after emulsification by triggering changes in the surfactant effectiveness, 15,16 and examples of the latter include stimuli-responsive or cleavable surfactants. 17 Owing to this unique morphological response to targeted chemical stimuli, Janus emulsions have been exploited in a number of applications, including as tunable microlenses, 18 optical waveguides, [19][20][21] scaffolds for the fabrication of anisotropic solid objects, 22,23 motile particle systems, 24,25 and as transducers and signal amplifiers in improved chemo-and biosensing platforms. [26][27][28][29] Herein, we leverage the exquisitely sensitive chemicalmorphological coupling inside Janus emulsions for the development of a new simple and broadly applicable method for the quantitative characterization of surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with earlier reports on the materials, we found that when kept under normal conditions, complex droplets are stable on the timescale of weeks to months. 30,37,38 Their overall size, dispersity, and composition remain constant when they are submerged in the surfactant solution at room temperature without aggressive mechanical agitation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Capstone (formerly known as Zonyl) is a fluorinated surfactant with a hydrophilic poly­(ethylene oxide) head and a hydrophobic poly­(tetrafluoroethylene) tail. Recently, the combination of SDS and Capstone has been used to emulsify and stabilize dynamic complex emulsions comprising H-oil and F-oil. ,,, We chose perfluorooctanoic acid (PFOA) and the potassium salt of perfluorooctane sulfonate (PFOS) because they are the two most studied PFAS compounds. ,, Cetrimonium bromide (CTAB) and Triton X-100 are both hydrocarbon surfactants and were chosen as the model compounds for cationic and nonionic surfactants, respectively.…”
Section: Experimental Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic multiphase emulsion droplets that can respond to marginal changes in their chemical environment offer a promising alternative for developing an easily applicable on-site quantification platform. Responsive Janus emulsions constitute double emulsions, with two phases aligned with gravity that present internal morphologies, that are exclusively controlled by the balance of interfacial tensions acting at the individual interfaces. , Using stimuli-responsive surfactants, the morphologies of Janus emulsions can be dynamically switched between encapsulated and Janus shapes. Due to their sensitive interfaces, Janus droplets have been demonstrated to respond to small changes in their chemical environment via induced droplet morphological changes (morphological assay) or a change in their orientation (agglutination assay) to report the presence of small molecular analytes (e.g., carbohydrates and caffeine) as well as a series of biological entities (e.g., bacteria, viruses, and enzymes). ,, In these sensing paradigms, marginal variations in the balance of the interfacial tensions at the external interfaces suffice to completely invert droplet morphology from an encapsulated double emulsion to an inverted encapsulated state . The diffusion-controlled response of Janus emulsions to variations in the balance of interfacial tensions can be leveraged to report small variations in surfactant effectiveness, which includes the surfactant type, ratio, concentration, and their critical micelle concentration …”
Section: Introductionmentioning
confidence: 99%